Digital Business Model Development for PT. Ascada Musik Indonesia - Setiawan, Affan; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2019)
Abstract - In the year of 2010, PT. Sutera Indomusik which has been establish since 1997 and many others local records label company is went bankrupt. The main reason of the bankruptcy is because the records company is focusing on selling physical records such as CD (compact disc) and cassettes while the piracy activity in Indonesia is still very high and seems uncontrolled. Two years later, Mr. Dicky as the owner of PT. Sutera Indomusik is establish the new company called PT. Ascada Musik with the main focus are to thrive in digital music businesses. Digital music are the terms used by music industry to define how the product is being sold on the market. If the music is sold by pay the CD or cassettes fee, then it is called physical and if the music is sold by paying download fee or subscribing fee or streaming fee then it is called digital. Since its establishment, Ascada Musik is successfully achieve its goal which is success on digital music businesses especially on Ring back tone (RBT) and full track download. For years, Ascada Music is mainly focus on RBT and full track download sales but as mention from IFPI (International Federation of Phonographic Industry) music reports, the revenue recorded from digital (RBT and full track) is going down every year. This trend is followed by another trend which is streaming technology because along with the decline of revenue by RBT and full track the revenue from streaming is increasing. So this is a phenomenon that happen in digital music industry and It is not align with the business strategy of Ascada Music since it is still focus on RBT and full track only. So the objective of this research are to analyze the internal and external factors of Ascada Music that influenced the company digital music business and to develop new strategies according to the current phenomena. The research methodology will be divided into three parts, first is to do the literature study to analyze the internal and external factor of the company using tools/platform then the second is building an interview protocol and selecting comprehensive stakeholder to be interviewed and collecting and analyzing the data from the interview. Last, based on the first and second step researcher compose a strategy suggestion for the company. Based on analysis, it is clear that the way people consume music is changing and Ascada Musik is not ready for that. This is influence the digital business of Ascada Musik because more of the customer is consuming music by streaming (audio and video) and leaving RBT and full track download which is the current focus of Ascada Musik. So Ascada Music should align its focus with the phenomena and develop new strategies to success. In the end, researcher has developed the recommendation business strategies and implementation plan for Ascada Musik. This implementation plan consists of three parts which is short term plan for plan under one-year time, medium term plan for plan between 1-3 years plan then the long-term plan for plan from 3 to 5 years. Hopefully the implementation plan can guide Ascada Musik to develop their digital business.Keywords: Digital Music, RBT, full track, streaming, business strategy